VD_FINDINFO Arrêt / 2019 / 1074 vom 26. November 2019 - VD Tribunal cantonal (2019)
PRÉVOYANCE PROFESSIONNELLE, SURASSURANCE, RENTEEN GÉNÉRAL, ADMISSION PARTIELLE, RESTITUTIONEN GÉNÉRAL | 24 LPP, 25 LPP, 26 LPP, 34a LPP, 35a LPP, 24 OPP2